Visual Content Exposure on the @Folkative Instagram Account to Increase Reading Interest Among Students of SMAN 3 Cibinong - Kusnandar, Muhammad Qidam; Santoso, Hudi; Ulya, Enden Darjatul; Pranata, Rici Tri Harpin (Lembaga Riset Mutiara Akbar, 2025)
The purpose of this study was to examine the effectiveness of visual content on the Instagram account @folkative and its impact on the interest in reading information at SMAN 3 Cibinong students. This study used a quantitative approach with a descriptive correlational method. The required sample was 94 respondents, obtained through the Slovin formula and purposive sampling technique. The statements used in the study have passed the validity and reliability testing process, with all statements declared valid and reliable. The results of the descriptive analysis showed that the visual content of @folkative was considered quite effective to effective, with most indicators being above the average value. Students' interest in reading information was in the good category. The results of the Pearson correlation test showed a strong and significant positive relationship between the effectiveness of visual content and students' interest in reading information. Furthermore, the regression analysis revealed that the effectiveness of visual content contributed 48.4% to students' interest in reading information. Thus, it can be concluded that the visual content of Instagram @folkative plays a role in increasing students' interest in reading information at SMAN 3 Cibinong.